2010
DOI: 10.1177/0741932510375469
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self-Regulated Strategy Development on the Writing of Expository Essays for Adults With Written Expression Difficulties

Abstract: A multiple-probe, multiple-baseline, across-subjects design was used to examine the writing performance of four low-achieving adult students with and without disabilities enrolled in general equivalency diploma (GED) preparatory classes. Students' writing was evaluated before instruction and after self-regulated strategy development (SRSD) instruction for the POW (Pick my idea-pay attention to the prompt, Organize, Write and say more) + TREE (Topic sentence, Reasons, Explanations, Ending) + COPS (Capitalize, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 16 publications
(24 reference statements)
3
24
0
5
Order By: Relevance
“…The strategy has been adapted for young developing writers in second and third grade (Graham, Harris, & Mason, 2005;Harris, Graham, & Mason, 2006) and for adult writers studying for a high school equivalency exam (Berry & Mason, 2012).…”
Section: Srsdmentioning
confidence: 99%
“…The strategy has been adapted for young developing writers in second and third grade (Graham, Harris, & Mason, 2005;Harris, Graham, & Mason, 2006) and for adult writers studying for a high school equivalency exam (Berry & Mason, 2012).…”
Section: Srsdmentioning
confidence: 99%
“…Self‐regulation can support students’ independence (Berry & Mason, ; Harris & Graham, ). Therefore, students were taught how to set goals and manage the writing task and their overall writing performance.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous research studies have demonstrated the positive effects of strategy instruction on writing performance in elementary and secondary school (Graham, Harris, & McKeown, ). Some research has found positive effects of strategy instruction in adults preparing for the GED (Berry & Mason, ) and college students with learning disabilities (Butler, Elaschuk, & Poole, ). This current study adds to the research conducted on strategy instruction by increasing understandings of how students modify strategies and how they move toward the flexible use of strategies.…”
Section: Strategy Instruction In Developmental Writingmentioning
confidence: 99%
“…[42,43] It is thus not surprising that writing interventions addressed to improve strategy development and self-regulation in writing have been proven to be particularly effective with children with learning disabilities, [43,45,68,69] as well as with children showing other kinds of developmental disorders. [70,71] It is therefore strange that instructional programmes addressing the development of writing strategies and self-regulatory skills in writing have been only rarely tested with children who are deaf [35] and, to the best of our knowledge, have been never tested with children with CIs.…”
Section: Use Procedural Facilitation To Tackle Children's Verbal Wm Dmentioning
confidence: 97%